If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49 + -6x = 21x + 19 Reorder the terms: 49 + -6x = 19 + 21x Solving 49 + -6x = 19 + 21x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21x' to each side of the equation. 49 + -6x + -21x = 19 + 21x + -21x Combine like terms: -6x + -21x = -27x 49 + -27x = 19 + 21x + -21x Combine like terms: 21x + -21x = 0 49 + -27x = 19 + 0 49 + -27x = 19 Add '-49' to each side of the equation. 49 + -49 + -27x = 19 + -49 Combine like terms: 49 + -49 = 0 0 + -27x = 19 + -49 -27x = 19 + -49 Combine like terms: 19 + -49 = -30 -27x = -30 Divide each side by '-27'. x = 1.111111111 Simplifying x = 1.111111111
| 8n+25=9n | | 5n^3-10n^2+3n-6= | | 13-7x=53-21x | | 6.7a-13.4=2.8a+110.23 | | (2x+3y)+(3x-y+2)=80 | | 112-2x=16x+20 | | 2x+3y=40 | | 2x+8=x+12 | | 2x+3z=22 | | y=x*8+30 | | 50=5(4-4x) | | a(a-2)-a=a(a+1)-8 | | 2(2x^3+3)=0 | | 6y+6=29 | | 2x-x+4,5=8,5 | | 6x+69=13x-8 | | 2x+31=10-49 | | x-30/8=x-102/2 | | -5x+2=x+8 | | x-102/2 | | 3x+60=7x+25 | | 108-3x=15x+24 | | 5x-7=3x+6 | | 11-10x=191-45x | | x*3+x*3= | | -7+x/2=22 | | 59-4x=10x+59 | | 9-12b+4b^2=0 | | 225-5x=31+17 | | 5r+12=3t+15 | | 2y-(7-4y)=10y-(y-1) | | 10w-10=15 |